Models of intervention and social support given to pregnant ad-olescents: a sociological study applied in the city of Portoviejo, Ecuador - José , Mendoza Velazco Derling; Menéndez , Fabián Gustavo Menéndez; Azúa , Iris María Sánchez; Saltos , María Fernanda Linzan (Journal of Ecohumanism, 2024)
Adolescent pregnancy represents a social and public health problem in several Latin American countries. In Ecuador, the city of Portoviejo has registered high rates of this phenomenon. Social workers provide comprehensive support to these adolescent mothers. However, there is a lack of research on the intervention models applied. The objectives were to determine the most frequent intervention models used by hospital social workers and to analyze the reasons for the care requested by pregnant adolescents. A multi-method study was conducted with a sequential explanatory design. A survey was carried out with 19 social workers and an interview with 4 social work experts. Data were analyzed statistically and by content analysis. Among the main results, the community model was found to be the one most used by social workers. The main problems were lack of family and financial support. Individualized care was the most provided. Adolescents sought assistance for lack of counselling, medical needs and emotional crises. It can be concluded that there is a need to strengthen community-based and comprehensive approaches with emphasis on education and family support. Future studies could include adolescents learning about their perspectives.